POSITION OF THE TEMPURAN VILLAGE HEAD IN THE IMPLEMENTATION OF VILLAGE AUTONOMY - Nitaria Angkasa; Rendi Evardi (Center for Constitutional and Legislative Studies University of Bandar Lampung, 2022)
The role of the village head in implementing village-scale local authority as a form of village autonomy according to Law Number 6 of 2014 concerning Villages is the authority to regulate and manage the interests of village communities that have been carried out by the village or are capable and effectively carried out by the village. Authority based on the right of origin and local authority on a village scale is a good opportunity for the village to be able to determine its own destiny in planning, implementing and evaluating development in the village. Villages have a large space to map various village assets and use them as much as possible for the benefit of the village. This study uses an empirical juridical approach. The empirical juridical approach is to conduct research in the field, namely by looking at the existing facts regarding the position of the village head in the application of regional autonomy. The result of this research is that the Head of Tempuran Village, Trimurjo District, Central Lampung Regency conveys the role of the Village Head regarding regional autonomy and village autonomy is very important. Law Number 23 of 2014 concerning Regional Government provides a strong foundation for villages in realizing a “Development Community” where the village is no longer an administrative level or regional subordinate but on the contrary as an “Independent Community”. The village and its community have the right to speak for the interests of the community itself. Villages are given the authority to regulate their villages independently, including in the social, political and economic fields. With this independence, it is hoped that it will increase the participation of rural communities in social and political development.